Acral lentiginous melanoma of the finger. Case report. - Orozco - Bobadilla , I-; Berumen, B. R; Mozqueda - Medina J. I, J. I; Moran - Martínez , J. (Revista de Ciencias Médicas Torreón, 2026)
Acral lentiginous melanoma (ALM) is a subtype of cutaneous melanoma that primarily affects the palms, soles, and subungual regions. We present the case of a 60-year-old male with a history of smoking (with a non-significant pack-year index), active alcohol use since youth, and type 2 diabetes mellitus (diagnosed 6 years prior and treated with glimepiride, metformin, and insulin glargine); his remaining medical history was unremarkable. He presented with a pigmented nail disorder that had been evolving for approximately 10 months, prompting him to seek a dermatology consultation. Upon specialist evaluation, a suspected diagnosis of a malignant pigmented nail lesion was established, and a biopsy protocol was initiated. In this patient, the relatively early identification of the lesion allowed for diagnosis at a localized stage, with favorable histopathological characteristics and the prospect of conservative management of the digit.